2018
DOI: 10.1186/s12884-018-1660-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for stillbirths: how much can a responsive health system prevent?

Abstract: BackgroundThe stillbirth rate is an indicator of quality of care during pregnancy and delivery. Good quality care is supported by a functional heath system. The objective of this study was to explore the risk factors for stillbirths, particularly those related to a health system.MethodsThis case-control study was conducted in two districts of Bihar, India. Information on cases (stillbirths) were obtained from facilities as reported by Health Management Information System; controls were consecutive live births … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 40 publications
3
36
0
1
Order By: Relevance
“…The findings of this study showed that the cumulative incidence of stillbirth was 9.48 per 1000 live birth. In a study conducted by Tshibumbu et al, 2014 in Namibia, the rate of stillbirth was reported as 12 per 1000 births [18], and the incidence of the stillbirth in hospital in few months was 8% or 80 per associated with stillbirth, which was in line with the results of our study [21][22][23][24][25][26]. Gestational hypertension increases the risk placenta to be separated earlier by twofold, leading to fetal-growth disorders, by increasing the risk of maternal mortality by threefold [27].…”
Section: Maternal Predictorssupporting
confidence: 91%
“…The findings of this study showed that the cumulative incidence of stillbirth was 9.48 per 1000 live birth. In a study conducted by Tshibumbu et al, 2014 in Namibia, the rate of stillbirth was reported as 12 per 1000 births [18], and the incidence of the stillbirth in hospital in few months was 8% or 80 per associated with stillbirth, which was in line with the results of our study [21][22][23][24][25][26]. Gestational hypertension increases the risk placenta to be separated earlier by twofold, leading to fetal-growth disorders, by increasing the risk of maternal mortality by threefold [27].…”
Section: Maternal Predictorssupporting
confidence: 91%
“…The WHO has reported that deficiencies in the quality of antenatal care play significant role in increasing stillbirth rate (28). A wise coverage of basic antenatal care can prevent a significant proportion of stillbirths (29). Afulani reported a decrease in the odds of having a stillbirth by half with a high quality of antenatal care (30).…”
Section: Discussionmentioning
confidence: 99%
“…It is imperative, therefore, to increase our attention for stillbirths and preterm birth interventions, which will positively impact on the maternal and newborn health outcomes (31). Investing in the health care system and providing a good quality and timely maternal services may prevent significant ratio of stillbirths (29).…”
Section: Discussionmentioning
confidence: 99%
“…It is imperative, therefore, to increase our attention for stillbirths and preterm birth interventions, which will positively impact the maternal and newborn health outcomes (31). Investing in the health care system and providing good-quality and timely maternal services may prevent a signi cant ratio of stillbirths (32). In interpretation of the study ndings, one should consider that the study of speci c causes of stillbirth has been hampered by lack of investigations such as fetal autopsy and genetic evaluation.…”
Section: Discussionmentioning
confidence: 99%